PENERAPAN PEMBERIAN HIBAH BERDASARKAN PASAL 920 KITAB UNDANG-UNDANG HUKUM PERDATA DILIHAT DARI ASAS LEGITIEME PORTIE (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 2954K/PDT/2017) - Vanessa Vanessa; Stanislaus Atalim (Jurnal Hukum Adigama, 2019)
The problem that often occurs in the case of grants is that legal grants are often found or grants that are legally flawed or canceled. The event of a grant which was declared legally flawed was also found in the case of the Decision of the Supreme Court of the Republic of Indonesia Number 2954K/Pdt/2017. Article 920 of the Civil Code about reduced, by which the article is not listed in the decision. On this basis, a problem arises namely how the application of grants based on Article 920 of the Civil Code can be seen from the principle of legal inheritance share. In answering these problems, the author uses normative legal research methods. Based on the results of the study, it can be seen that with the cancellation of the grant deed by the court's decision and if the heirs who demanded the cancellation of the grant be accompanied by demanding a legal inheritance share, a reduction must be made. Then the author can conclude that the implementation of Article 920 of the Civil Code important to be carried out by the heirs concerned, because by the judge's decision regarding the distribution according to legal inheritance share, so the Article 920 of the Civil Code automatically applicable. The advice that can be given is better for the community to distribute inheritance and provide grants during their lifetime in a fair and equitable manner to avoid problems regarding the grant being declared null and void.